End user engagement in refugee shelter design: Contextualising participatory process. (May 2022) - Hart, Jason; Albadra, Dima; Paszkiewicz, Natalia; Adeyeye, Kemi; Copping, Alex
Abstract : Debate about participatory design (PD) has focussed considerably upon process. Factors such as facilitation skills and commitment to a participatory ethos have been highlighted as factors mediating stakeholder engagement. Discussion has been driven overwhelmingly by experience of PD in the global North with citizens who enjoy full rights. This article considers engagement with encamped refugees in the global South. Here context has a significant impact upon engagement. Drawing on a four-year research project concerning shelter design we discuss dimensions of context that bear particularly upon PD efforts. As we illustrate, despite contextual constraint, it is possible to produce valuable knowledge about design together with residents. Moreover, attention to context can help achieve a more nuanced approach to the evaluation of PD initiatives. Highlights: Pursuit of PD in refugee camps reveals the impact of context upon end-user engagement. Evaluation of end-user engagement in PD initiatives might productively embrace consideration of context. PD efforts benefit greatly from a multi-disciplinary approach employing diverse methods.